2014
DOI: 10.1097/gme.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

A standardized exercise intervention differentially affects premenopausal and postmenopausal African-American women

Abstract: Objective African American women present an understudied population in menopause research, yet face greater post-menopausal challenges associated with mortality than their white peers. We investigated the effect of a mild-intensity aerobic exercise training program on markers of mortality risk in both pre- and post-menopausal African American women. Methods 16 pre- and 19 post-menopausal women underwent 6 months of mild-intensity aerobic exercise training. Measurements included markers of blood lipid and glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…101 Even small amounts of physical activity are protective against health decline in older adults. 55 Activities do not have to be done at one time, but can be spread throughout the day in shorter time allotments. Reduction in sedentary behavior (sit less, move more) in addition to the addition of light activity should be emphasized as a goal for older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…101 Even small amounts of physical activity are protective against health decline in older adults. 55 Activities do not have to be done at one time, but can be spread throughout the day in shorter time allotments. Reduction in sedentary behavior (sit less, move more) in addition to the addition of light activity should be emphasized as a goal for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that although mild-intensity aerobic exercise training improves some markers of cardiovascular disease and mortality in postemenopausal women, additional markers of mortality risk (ie, aerobic fitness, glomerular filtration rate, BMI, plasma glucose dysfunction, markers of endothelial dysfunction) only improve in premenopausal African-American women. 55 Additional studies are needed to evaluate the ethnic and racial differences exercise may have on menopausal women.…”
Section: Maintenance Of Weight and Healthy Body Compositionmentioning
confidence: 98%
“…Circulating EMPs are increased in overweight/obese individuals with metabolic syndrome [ 32 ] and in various cardiovascular diseases [ 47 ]. Due to the benefits of exercise on endothelial function and recent evidence that traditional moderate-intensity endurance training can reduce EMP levels [ 48 50 ], we hypothesized that acute high-intensity exercise would lead to reduced EMPs in overweight/obese participants. Our results revealed a clear sex difference in EMP responses to exercise and this hypothesis was only supported for males.…”
Section: Discussionmentioning
confidence: 99%
“…However, the participants in this study were tested after completing several weeks of exercise training (including HIIE) and our participants were inactive prior to the experimental exercise trials. It is possible that exercise training, which is well known to improve endothelial function [ 4 ] and recently reported to reduce EMPs [ 48 50 ], may have reduced baseline EMPs in the fit cardiac rehabilitation patients studied by Guiraud and colleagues [ 54 ] such that acute exercise had limited effects. Future studies are needed to examine acute and chronic EMP responses to high-intensity exercise in individuals at elevated risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other studies, concluding that estrogen is essential for exercise-induced improvements in risk factors for CVD, consisted of moderate-intensity walking interventions with HR between 50-65% and 65-80% of _ Vo 2max . 15,16 Earlier, we showed that floorball training, also classified as high-intensity exercise, caused an increase in _ Vo 2max among postmenopausal women. 17 Which also implies that intense exercise training Original Research GYNECOLOGY ajog.org ajog.org…”
Section: Study Strengths and Limitationsmentioning
confidence: 96%